Against the odds: A case study of technology acceptance and successful IS implementation in the community health sector - Schaper, Louise; Pervan, Graham (Health Informatics Society of Australia, 2005)
This paper examines technology acceptance and use and the associated individual and organisational impacts within a small non-profit, community-based health care organisation. The study described involved a longitudinal multi-method investigation, collecting quantitative and qualitative data over a 7-month period, timed in conjunction with the implementation of a new information system infrastructure. A research model is proposed and explored. The substantial data collected enables comprehensive analysis of the links between technology acceptance and use with the outcomes and impacts of use on individual and organisational goals. Results from this study provide qualitative support for the proposed model, demonstrate the invaluable role of individual commitment to the organisation and to the matching of organisational and individual goals and discusses how the IS implementation was successful, despite numerous barriers and challenges. Results also highlight the importance of qualitative methodologies in information systems research. The significance of this work and the implications of the findings are discussed.